Subcutaneous nodules of the face: an unusual presentation of Darier–Roussy disease - Sofia Hermosilla; Isidora Wajner; Alberto Lara; Claudio Toloza; Carlo Lozano; Eduardo Rozas; Antonio Guglielmetti; José Hono (Clinical and Experimental Dermatology, 2026)
Subcutaneous sarcoidosis (Darier–Roussy disease) is an uncommon form of cutaneous sarcoidosis that predominantly affects the extremities. Facial involvement is rare and may represent a diagnostic challenge. We describe a woman presenting with nodules of the cheek and lips, whose histopathological and radiological findings led to the diagnosis of systemic sarcoidosis. This case expands the clinical spectrum of subcutaneous sarcoidosis and emphasizes the need to consider sarcoidosis in the differential diagnosis of granulomatous panniculitis affecting the face.